Exploring Social Networks with Matrix-based Representations - Henry Riche, Nathalie (2008)
I conduct my research in the general field of human-computer interaction, with a primary interest in information visualization. My dissertation research deals with the visual exploration of large social networks, bridging graph theory, social network analysis, information visualization and human-computer interaction. I aim at designing, implementing and evaluating novel interactive visualization techniques. I recently graduated and received a joint Ph. D. in Computer Science in France and in Australia. My co-advisors were Pr. Jean-Daniel Fekete (INRIA, France) and Pr. Peter Eades (University of Sydney, Australia). I started my Ph.D. research in october 2004 and defended on the 3rd july 2008, receiving my Ph.D. with honors.